2015
DOI: 10.1515/oph-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron transmission for the analysis of the interface barrier formation and the density of the unoccupied electronic states in the ultra-thin layers of fluorinated copper-phthalocyanine

Abstract: Abstract:The interfacial structure made from the thermally deposited 5 -7 nm thick layers of hexadecafluoro copper phthalocyanine (F 16 -CuPc) and of the unsubstituted copper phthalocyanine (CuPc) was subjected to the studies. The surface work function and the density of the unoccupied electron states (DOUS) located 5-20 eV above the Fermi level (E F ) were investigated during the CuPc/F 16 -CuPc interface formation using the very low energy electron diffraction (VLEED) method and the total current spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Their energy position corresponds well to the position of the peaks B 1 -B 8 of the DOUS obtained from the TCS experiment (Fig.2b). The three unlabeled peaks of the calculated DOUS in Fig.2c situated in the energy range from 2 eV to 5 eV correspond well to the three low-lying DOUS peaks observed by the other authors in the C 60 vacant band, for which the * character was suggested [2,15,38]. The DOUS bands in the energy range from 5 eV to 7 eV, marked as the maxima C 1 , C 2 in Fig.2b and B 1 , B 2 in Fig.2c are analogous to the bands which were assigned as * bands according to the refs.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Their energy position corresponds well to the position of the peaks B 1 -B 8 of the DOUS obtained from the TCS experiment (Fig.2b). The three unlabeled peaks of the calculated DOUS in Fig.2c situated in the energy range from 2 eV to 5 eV correspond well to the three low-lying DOUS peaks observed by the other authors in the C 60 vacant band, for which the * character was suggested [2,15,38]. The DOUS bands in the energy range from 5 eV to 7 eV, marked as the maxima C 1 , C 2 in Fig.2b and B 1 , B 2 in Fig.2c are analogous to the bands which were assigned as * bands according to the refs.…”
Section: Resultssupporting
confidence: 85%
“…[2,15,[38][39][40] and using the DOUS obtained as a result of the DFT calculations (Fig.2c). The calculations at the B3LYP/6-31G(d)) level provided over 150 values of the orbital energies in the energy range from 0 eV to 25 eV, the scaled virtual orbital energies (see section 2) were used to plot the DOUS function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation